A self-contained interactive iteration positioning and orientation coupled navigation method based on skylight polarization. (June 2021) - Zhang, Jie; Yang, Jian; Wang, Shanpeng; Liu, Xin; Wang, Yan; Yu, Xiang
Abstract: The global positioning and orientation determination of marine vehicles is a challenging issue, especially in the distant sea scenarios where global navigation satellite system (GNSS) and/or magnetic compass failure. In this paper, a self-contained interactive iteration positioning and orientation coupled navigation method based on skylight polarization is proposed. To be more specific, by fusing the e-vectors and the gravity vectors, the orientation determination step is presented. Accordingly, the pitch, yaw, and roll angles can be calculated, and introduced into the global positioning step. In combination with the two steps, a coupled iteration mechanism of global positioning solution and orientation determination based on skylight polarization is constructed. According to the coupled iteration mechanism, the polarization-based geolocation and orientation can be thereby calculated under the complex scenarios where the GNSS or magnetic compass are disturbed. Finally, a set of simulations and field tests are carried out to validate the performance of the method.